Research on the Stability of a Rabbit Dry Eye Model Induced by Topical Application of the Preservative Benzalkonium Chloride - Li, Chaoyang (Public Library of Science, 2012)
BACKGROUND: Dry eye is a common disease worldwide, and animal models are critical for the study of it. At present, there is no research about the stability of the extant animal models, which may have negative implications for previous dry eye studies. In this study, we observed the stability of a rabbit dry eye model induced by the topical benzalkonium chloride (BAC) and determined the valid time of this model. METHODS AND FINDINGS: Eighty white rabbits were randomly divided into four groups. One eye from each rabbit was randomly chosen to receive topical 0.1% BAC twice daily for 2 weeks (Group BAC-W2), 3 weeks (Group BAC-W3), 4 weeks (Group BAC-W4), or 5 weeks (Group BAC-W5). Fluorescein staining, Schirmer's tests, and conjunctival impression cytology were performed before BAC treatment (normal) and on days 0, 7, 14 and 21 after BAC removal. The eyeballs were collected at these time points for immunofluorescence staining, hematoxylin and eosin (HE) staining, and electron microscopy. After removing BAC, the signs of dry eye in Group BAC-W2 lasted one week. Compared with normal, there were still significant differences in the results of Schirmer's tests and fluorescein staining in Groups BAC-W3 and BAC-W4 on day 7 (P<0.05) and in Group BAC-W5 on day 14 (P<0.05). Decreases in goblet cell density remained stable in the three experimental groups at all time points (P<0.001). Decreased levels of mucin-5 subtype AC (MUC5AC), along with histopathological and ultrastructural disorders of the cornea and conjunctiva could be observed in Group BAC-W4 and particularly in Group BAC-W5 until day 21. CONCLUSIONS: A stable rabbit dry eye model was induced by topical 0.1% BAC for 5 weeks, and after BAC removal, the signs of dry eye were sustained for 2 weeks (for the mixed type of dry eye) or for at least 3 weeks (for mucin-deficient dry eye).